Effects of deletion of the ac109 gene of Autographa californica nucleopolyhedrovirus on interactions with mammalian cells - Alfonso, Victoria; Amalfi, Sabrina; Lopez, Maria Gabriela; Taboga, Oscar Alberto (2017)
Baculoviruses are able to enter into mammalian cells, where they can express a transgene that is placed under an appropriate promoter, without producing infectious progeny. ORF109 encodes an essential baculovirus protein that participates in the interaction of the baculovirus with mammalian cells. To date, the mechanisms underlying this interaction are not yet known. We demonstrated that although a Ac109 knock out virus maintained its ability to enter into BHK-21 cells, there was a marked reduction in the expression efficiency of the nuclear transgene. Moreover, the amount of free cytoplasmic viral DNA, which was detected by transcription of a reporter gene, was severely diminished. These results suggest Ac109 could be involved in maintaining the integrity of the viral nucleic acid.